Decision Support System Determining Salary Increase Using the Sugeno Method at Pt. Sumatra Tobacco Trading Company - Tri Wahyuning Tiyas Achiriani (International Journal of Basic and Applied Science, 2021)
PT. STTC is a company engaged in the manufacture of cigarettes. In an effort of improving the performance of employees at PT. STTC giving salary increases to employees who have good performance. In granting salary increases are sometimes not in accordance with the results of its performance. Granting salary increases are often on average, or sometimes the granting of salary increases only with estimate only, without application of the calculation. For that is the need for decision support system of determining salary increases. For that is the need for decision support system of determining salary increases. one of the methods in use are using the method of fuzzy logic sugeno. The method selected for being able to complete the assessment of the performance of employees on the basis of criteria that are already in the set.